KEEFEKTIFAN LAYANAN BIMBINGAN KLASIKAL UNTUK MENINGKATKAN RASA PERCAYA DIRI PADA REMAJA DI PANTI ASUHAN PASAR BAWAH - Egista Karningsih; Syawaluddin (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2024)
In the process of adjusting to oneself in an orphanage, of course there are obstacles that interfere with carrying out one's role in the group. Factors that influence teenagers' difficulty in adapting themselves to their environment are a lack of confidence in their own abilities, which is usually called a lack of self-confidence. This problem will affect adolescent behavior. The research method that will be used is descriptive quantitative. With a population of children from the lower market Aisiyah orphanage, as well as a sample of teenagers who have low self-confidence. The instrument used in this research is a measurement scale. A measurement scale was developed to measure how much bullying behavior a student has. The data analysis technique uses the Wiloxon rank test. The pretest score was obtained with a score of 310 and a posttest score of 461, the results of the measurement scale were very effective because the hypothesis was accepted, the Wilcoxon test results showed that the Aaymp.sig value was 0.012, less than 0.05, therefore there was a difference in the pretest and posttest scores in the application of guidance services classic.